2008
DOI: 10.1021/jm070279v
|View full text |Cite
|
Sign up to set email alerts
|

(Phenylpiperazinyl-butyl)oxindoles as Selective 5-HT7 Receptor Antagonists

Abstract: A series of potent 5-hydroxytryptamine 7 (5-HT 7) ligands has been synthesized that contain a 1,3-dihydro-2 H-indol-2-one (oxindole) skeleton. The binding of these compounds to the 5-HT 7 and 5-HT 1A receptors was measured. Despite the structural similarity of these two serotonin receptor subtypes, several derivatives exhibited a high selectivity to the 5-HT 7 receptor. According to the structure-activity relationship observations, compounds unsubstituted at the oxindole nitrogen atom and containing a tetramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 53 publications
6
82
0
1
Order By: Relevance
“…Volk et al reported the alkylation of oxindoles in the 3-position with primary alcohols using Raney W Nickel [20][21][22]. According to Shilov et al, this type of reaction can be referred as an indirect C-H activation [6], while others characterized this catalytic reaction as "borrowing hydrogen" methodology [23].…”
Section: Resultsmentioning
confidence: 99%
“…Volk et al reported the alkylation of oxindoles in the 3-position with primary alcohols using Raney W Nickel [20][21][22]. According to Shilov et al, this type of reaction can be referred as an indirect C-H activation [6], while others characterized this catalytic reaction as "borrowing hydrogen" methodology [23].…”
Section: Resultsmentioning
confidence: 99%
“…[13] Therefore, we tested our catalytic system on the benzylation of oxindole (9). However, we found that only 15 % of the oxindole was benzylated under the reaction conditions described above, presumably due to the fact that the methylene group of 9 is less reactive than those in 1,3-dicarbonyls 1 and 7.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, studies have revealed the critical role of the arylpiperazine substitution pattern in determining the receptor affinity. Volk et al 46 found out that electron-donating substituents (-OCH 3 ) were superior to electron-withdrawing (-Cl, -F) for binding to the 5-HT 1A and 5-HT 7 receptors. Our study confirmed that 2-F and 3-CF 3 substituents at the phenyl ring of arylpiperazine were highly preferential for the 5-HT 1A R over the 5-HT 7 R. The influence of substituents 2-F and 3-CF 3 on 5-HT 7 receptor affinity in the group of tested compounds appears to be equivocal, and a spectrum of activities was observed.…”
Section: Biological Evaluationmentioning
confidence: 99%